2013
DOI: 10.5858/arpa.2013-0539-oa
|View full text |Cite
|
Sign up to set email alerts
|

The Presence of Anti-HLA Donor-Specific Antibodies in Lung Allograft Recipients Does Not Correlate With C4d Immunofluorescence in Transbronchial Biopsy Specimens

Abstract: Context.—C4d immunofluorescence (IF) is a surrogate for development of donor-specific antibodies (DSAs) against human leukocyte antigen (HLA) class I and II antigens in kidney and heart biopsy specimens for monitoring of antibody-mediated (humoral) allograft rejection (AMR). Use of C4d IF in monitoring of lung allografts has shown conflicting results. Objective.—To determine if C4d IF can be used as a reliable marker for AMR and if it correlates with the presence of DSAs and histologic findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…There are currently three limitations of C4d staining in LT biopsies: (i) sampling-related limitations (TBB provides randomly limited tissue sampling), (ii) technical constraints, and (iii) positivity interpretation. Previous studies have explored different C4d staining techniques including immunofluorescence (38,39), immunohistochemistry (40)(41)(42) and the use of either frozen or formalin-fixed, paraffin-embedded biopsies, with contradicting results. Besides AMR, C4d positivity can also be due to either nonspecific staining of noncomplement proteins (i.e.…”
Section: Antibody-mediated Rejectionmentioning
confidence: 99%
“…There are currently three limitations of C4d staining in LT biopsies: (i) sampling-related limitations (TBB provides randomly limited tissue sampling), (ii) technical constraints, and (iii) positivity interpretation. Previous studies have explored different C4d staining techniques including immunofluorescence (38,39), immunohistochemistry (40)(41)(42) and the use of either frozen or formalin-fixed, paraffin-embedded biopsies, with contradicting results. Besides AMR, C4d positivity can also be due to either nonspecific staining of noncomplement proteins (i.e.…”
Section: Antibody-mediated Rejectionmentioning
confidence: 99%
“…The identification of C4d staining on a biopsy sample as a surrogate marker for AMR due to activation of the complement cascade is controversial and its role in the diagnosis of pulmonary AMR may have been overestimated (56,61). It is rarely seen in patients with a diagnosis of pulmonary AMR based on other criteria (26,100), and there is poor inter-pathologist agreement when it comes to recognising a positive stain on trans-bronchial biopsy (101). Notably, C4d is not specific to pulmonary AMR, can be found in any process that is associated with complement activation such as reperfusion injury and infection (86), and studies have shown no little or correlation between positive staining and the presence of DSA (100,102).…”
Section: C4d Immunohistochemistrymentioning
confidence: 99%
“…Several primary studies reviewed in the summary statement, along with studies published since then, recognize that the correlation of C4d staining and donor-specific antibody studies in lung allografts may be loose, if not controversial, and will certainly require further study. 14,[77][78][79][80][81] Currently, analogous to other solid organ allografts, it is recommended that C4d staining in allograft lung tissue be scored in the interstitial alveolar capillaries only.…”
Section: Lungmentioning
confidence: 99%